2219. Syphilis Diagnosis and Treatment Practices in the Ambulatory Setting of a Large Vertically Integrated Healthcare Organization: An Opportunity for Infectious Diseases Physician Engagement. (15th December 2022) - Gwiazdon, Matthew; Matheu, Michelle M; Seibert, Allan M; Stanfield, Valoree K; Kumar, Naresh; Stenehjem, Edward A
Abstract: Background: Sexually transmitted infections (STIs) continue to increase in the United States. Syphilis management may challenge busy outpatient clinicians and diagnostic delays have been described. To better understand syphilis treatment practices and identify targets for improvement in our organization, we characterized outpatient encounters associated with a positive syphilis test. Methods: Intermountain Healthcare (IH) is an integrated healthcare system with 23 emergency departments (ED), 34 urgent care (UC), and >100 primary care (PC) clinics. Protocols favor treponemal testing as the initial screening test. All positive treponemal tests associated with a positive non-treponemal test in the ambulatory setting were routed to an electronic inbox within the electronic health record (EHR) and reviewed by a team of Infectious Disease (ID) clinicians from May 1 st 2021 – January 31 st, 2022. Positive results originating from ID or HIV-trained primary care clinicians were excluded. Each encounter was assessed for staging and treatment plans based on CDC guidelines as well as HIV pre-exposure prophylaxis (PrEP) and HIV treatment eligibility. Results: 119 encounters were reviewed. Patients 30-44 years old were most likely to have a positive test (50, 42.0%). PC (63, 52.9%) and UC (24, 20.2%) accounted for the most positive tests. 102 (85.7%) positive tests were from white patients, consistent with racial demographics of Utah. Only 40 (33.6%) encounters could be clinically staged after chart review by an ID clinician. Of these, 17 (42.5%) were determined to be staged and treated inappropriately by the treating provider. 54 (45.4%) encounters could not be staged and required further testing or more clinical history to determine the significance of positive test. 18 (15.1%) patients could possibly have benefitted from PrEP evaluation and one new HIV diagnosis was referred to ID clinic. Conclusion: Our exploratory analysis revealed many syphilis cases unable to be staged on chart review and opportunities to improve care. Strategies such as prospective audit and feedback or eConsults may be insufficient and clinical evaluation may be necessary to stage syphilis infection. Syphilis care improvements in our system may be a future target for ID physician engagement and novel stewardship strategies. Disclosures: All Authors : No reported disclosures.